VALIDITAS PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INDONESIA BERBANTUAN CANVA, BLOOKET, DAN GOOGLE DRIVE - Dewi Sintiya; Charlina; Tria Putri Mustika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop Indonesian language learning materials on anecdotal texts for 10th-grade high school students. The objectives of this learning material development are: 1) to determine how to develop Indonesian language learning materials using Canva, Blooket, and Google Drive for 10th-grade high school anecdotal texts, and 2) to determine the results of expert validation regarding the developed learning materials. The research method used is R&D (Research and Development), a type of research aimed at developing and validating a product. The selected development model is the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research instrument used was a questionnaire distributed to three validators (subject matter, media, and language experts). The research results showed that the subject matter expert provided 60 ratings, representing 100% of the total, and the product was categorized as “Highly Suitable.” furthermore, the assessment by the language expert yielded a total score of 54 with a percentage of 90%, and this validation score falls into the “Highly Acceptable” category; the assessment by the media expert yielded a score of 65 with an acceptability percentage of 93% and falls into the “Highly Acceptable” category.